The role of phonological and orthographic information in lexical selection. - Alario F; Schiller NO; Domoto-Reilly K; Caramazza A; Alario, F-Xavier; Schiller, Niels O; Domoto-Reilly, Kimiko; Caramazza, Alfonso (Brain & Language, 2003)
We report the performance of two patients with lexico-semantic deficits following left MCA CVA. Both patients produce similar numbers of semantic paraphasias in naming tasks, but presented one crucial difference: grapheme-to-phoneme and phoneme-to-grapheme conversion procedures were available only to one of them. We investigated the impact of this availability on the process of lexical selection during word production. The patient for whom conversion procedures were not operational produced semantic errors in transcoding tasks such as reading and writing to dictation; furthermore, when asked to name a given picture in multiple output modalities--e.g., to say the name of a picture and immediately after to write it down--he produced lexically inconsistent responses. By contrast, the patient for whom conversion procedures were available did not produce semantic errors in transcoding tasks and did not produce lexically inconsistent responses in multiple picture-naming tasks. These observations are interpreted in the context of the summation hypothesis (Hillis & Caramazza, 1991), according to which the activation of lexical entries for production would be made on the basis of semantic information and, when available, on the basis of form-specific information. The implementation of this hypothesis in models of lexical access is discussed in detail.